(untitled) (Psychology Travelogs, 2024)
The article is devoted to the highlighting of the psychological essence of the phenomenon of personal responsibility based on the analysis of its psychological components. The problem of responsibility draws the attention of researchers in various scientific spheres. The scope of research shows, first of all, the absolute importance of responsibility in all spheres of life. At the same time, the diversity of studies has led to a blurring of the content and essence of the concept of responsibility, as approaches to its study have been hardly correlated. Therefore, the current task for research in the problematic area of responsibility is primarily to analyse and integrate existing points of view through a comprehensive study of responsibility as an integral personal characteristic that regulates human behaviour in various life situations. In the current realities, modern Ukrainian psychology needs to study responsibility as a psychological phenomenon that is directly related to personal issues in extreme conditions of life and life safety. In general scientific research, responsibility is associated with such categories as choice, achievement, skills and capabilities of the personality. Responsibility is a basic quality of a personality, so its study involves the integration of various sciences: philosophy, sociology, law, ethics, pedagogy and psychology. From a life perspective, the role of responsibility is evident in all spheres of human and social life. From a scientific point of view, there have been attempts to conduct a broad comprehensive study of responsibility that would cover the most significant areas of a person’s life, the implementation of which directly depends on the person’s responsibility. According to a lot of researchers, responsibility is a central personal characteristic that determines the lifestyle and enables an individual to resolve contradictions and difficulties of life in an optimal way. The perception of the systemic nature of responsibility implies that it is not just one of the personality features, but its integral quality, a mechanism for organising human life, which significantly determines the quality and success of performance. Responsibility helps to achieve personal maturity and integration. Responsibility gives the person the opportunity to be a subject, an "author" of their life, confident in the ability to manage their own life, the ability to predict the future, comprehend the meaning of life and achieve life satisfaction.